2015
DOI: 10.1002/2015jb012288
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Stromboli's summit craters at the end of the 2007 effusive eruption detected by thermal surveys and seismicity

Abstract: This work arises from the field observations made during the civil protection emergency period connected to the 2007 Stromboli eruption. We observed changes in the shallow feeding system of the volcano to which we give a volcanological interpretation and the relative implications. Here we describe the processes that occurred in the upper feeding system from the end of the 2007 effusive eruption on 3 April to the renewal of the strombolian explosive activity at the summit craters (30 June), interpreted using mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…Conversely, the decrease of explosive activity following the lava flow output suggests that the drainage of the uppermost conduit was efficient, requiring a certain amount of time (of the order of h, Figure 3a) in order to allow the magma level to rise again after drainage in order to restore the persistent Strombolian activity at the summit craters. This is consistent with similar events, which were observed during the much longer 2002-2003 and 2007 effusive phases [19,39,[89][90][91]. Satellite data allowed us to obtain the map of the lava flows expanding on the SdF slope between 28 March and 1 April, which was estimated at 94,500 ± 3380 m 2 (Figure 6), the radiant heat flux over time (Figure 3e), and, consequently, the TADR ( Figure 5), providing an estimation of the cumulative erupted lava flow volume at 37-69 × 10 3 m 3 DRE.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, the decrease of explosive activity following the lava flow output suggests that the drainage of the uppermost conduit was efficient, requiring a certain amount of time (of the order of h, Figure 3a) in order to allow the magma level to rise again after drainage in order to restore the persistent Strombolian activity at the summit craters. This is consistent with similar events, which were observed during the much longer 2002-2003 and 2007 effusive phases [19,39,[89][90][91]. Satellite data allowed us to obtain the map of the lava flows expanding on the SdF slope between 28 March and 1 April, which was estimated at 94,500 ± 3380 m 2 (Figure 6), the radiant heat flux over time (Figure 3e), and, consequently, the TADR ( Figure 5), providing an estimation of the cumulative erupted lava flow volume at 37-69 × 10 3 m 3 DRE.…”
Section: Discussionsupporting
confidence: 91%
“…For each point, we measured the surface temperature by means of a handheld thermal camera FLIR SC640 kept at about 1 m over the soil using a tripod and shallow gradients using a graduated thermocouple inserted at various depths into the ground (for details on the usage of FLIR SC640 thermal camera, see, e.g., Marotta et al [40]; a summary of its technical characteristics is reported in Table 1). Surface thermal images were taken just before the insertion of the thermocouple to avoid perturbations to the shallow thermal system due to the presence of the thermocouple itself.…”
Section: Measurement Of the Soil Temperature By Ir Cameramentioning
confidence: 99%
“…During both the 2002-2003 and 2007 effusive eruptions the persistent summit explosive activity stopped or significantly decreased, as a result of magma drainage from the eruptive fissure [5,13,14]. After the 2007 effusive eruption, the persistent explosive summit activity of Stromboli resumed [48], but the eruptive activity changed, displaying several unusual overflows from the crater zone, a more than doubled number of major explosions, and absence of paroxysms [32,49,50]. The enhanced monitoring network allowed us to recognize that the effusive phases were preceded by a few weeks of increment of amplitude and occurrence rate of Very Long Period events (VLP) and associated number of explosions, which are related to the magma level within the shallow conduit [1,5,13,35].…”
Section: Introductionmentioning
confidence: 99%